1991
DOI: 10.1007/bf00293469
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesions in chronic granulomatous disease

Abstract: In chronic granulomatous disease (CGD) enzyme-deficient neutrophils and mononuclear cells lack the respiratory burst required for biocidal activity. Recurrent infections lead to granulomas in various organs but brain lesions are rare. In the present case, a 23-year-old male with numerous infections since early childhood died of overwhelming pulmonary aspergillosis. He first began to experience neurological deficits at the age of 17. Computerized tomography and magnetic resonance imaging revealed fleeting white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…14 Unlike the chronic type of optic nerve involvement in sarcoidosis, the acute form responds well to corticosteroid therapy, 15 as seen in patient 1. In contrast, central nervous system inflammation unrelated to infections is rare in CGD, and other than 1 report of brain lesions from postmortem findings, 16 all reported cases to date are related to fungal infections. 17 The prevalence of chorioretinal lesions in CGD is 23% to 35%, but they typically appear "punched out" and are associated with pigment clumping.…”
Section: Figurementioning
confidence: 93%
“…14 Unlike the chronic type of optic nerve involvement in sarcoidosis, the acute form responds well to corticosteroid therapy, 15 as seen in patient 1. In contrast, central nervous system inflammation unrelated to infections is rare in CGD, and other than 1 report of brain lesions from postmortem findings, 16 all reported cases to date are related to fungal infections. 17 The prevalence of chorioretinal lesions in CGD is 23% to 35%, but they typically appear "punched out" and are associated with pigment clumping.…”
Section: Figurementioning
confidence: 93%
“…Various pathogens have been associated with brain abscess development including Scedosporium prolificans [81], Alternaria infectoria [82], Salmonella enterica subspecies houtenae [83], and Aspergillus [84,85]. Other complications associated with CGD include white matter disease [86], CNS granulomatous disease [87] and leptomeningeal, and focal brain infiltration by pigmented, lipid-laden macrophages [88]. Several reports of fungal brain infection [89], Aspergillus abscess resembling a brain tumor [90], spinal cord infection by Aspergillus [91] and fungal granuloma of the brain have been described [92].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…In this case there was also a widespread involvement of the reticuloendothelial system. Had® eld et al 15 described a case in which pigmented macrophages laden with lipofuscin similar to those reported in CGD were found in the perivascular spaces and the leptomeninges; however, no infectious focus was found. Gentile et al 16 reported a case of focal cerebral lesions caused by aspergillus infection in children in which the source of infection was in the chest.…”
Section: Discussionmentioning
confidence: 61%